Statins Activate Human PPAR𝛼 Promoter and Increase PPAR𝛼 mRNA Expression and Activation in HepG2 Cells - Makoto Seo; Ikuo Inoue; Masaaki Ikeda; Takanari Nakano; Seiichiro Takahashi; Shigehiro Katayama; Tsugikazu Komoda (PPAR Research)
Statins increase peroxisome proliferator-activated receptor 𝛼 (PPAR𝛼) mRNA expression, but the mechanism of this increased PPAR𝛼 production remains elusive. To examine the regulation of PPAR𝛼 production, we examined the effect of 7 statins (atorvastatin, cerivastatin, fluvastatin, pitavastatin, pravastatin, rosuvastatin, and simvastatin) on human PPAR𝛼 promoter activity, mRNA expression, nuclear protein levels, and transcriptional activity. The main results are as follows. (1) Majority of statins enhanced PPAR𝛼 promoter activity in a dose-dependent manner in HepG2 cells transfected with the human PPAR𝛼 promoter. This enhancement may be mediated by statin-induced HNF-4𝛼. (2) PPAR𝛼 mRNA expression was increased by statin treatment. (3) The PPAR𝛼 levels in nuclear fractions were increased by statin treatment. (4) Simvastatin, pravastatin, and cerivastatin markedly enhanced transcriptional activity in 293T cells cotransfected with acyl-coenzyme A oxidase promoter and PPAR𝛼/RXR𝛼 expression vectors. In summary, these data demonstrate that PPAR𝛼 production and activation are upregulated through the PPAR𝛼 promoter activity by statin treatment.